Enterovirus infections in pediatric patients hospitalized with acute gastroenteritis in Chiang Mai, Thailand, 2015–2018 - Rojjanadumrongkul,Kitsakorn; Kumthip,Kattareeya; Khamrin,Pattara; Ukarapol,Nuthapong; Ushijima,Hiroshi; Maneekarn,Niwat (PeerJ, 2020)
Background Infection with viruses especially rotavirus, norovirus, astrovirus, and adenovirus has been known to be a major cause of acute gastroenteritis in children under 5 years of age globally, particularly in developing countries. Also, some genotypes of enteroviruses (EVs) have been reported to be associated with gastroenteritis. This study is aimed to investigate the prevalence and genotype diversity of EV in children admitted to hospitals with acute gastroenteritis. Methods A total of 1,736 fecal specimens were collected from children hospitalized with diarrhea in Chiang Mai, Thailand from 2015 to 2018. All specimens were tested for the presence of EV by RT-PCR of the 5′ untranslated region. The genotypes of EV were further identified by nucleotide sequencing and phylogenetic analysis of the viral protein 1 (VP1) gene. Results EV was detected in 154 out of 1,736 specimens (8.9%) throughout the study period. The prevalence of EV detected in 2015, 2016, 2017, and 2018 was 7.2%, 9.0%, 11.2%, and 8.6%, respectively. EV was detected all year round with a high prevalence during rainy season in Thailand. Overall, 37 genotypes of EV were identified in this study. Among these, coxsackievirus (CV)-A24 and CV-B5 (7.5% each), and EV-C96 (6.8%) were the common genotypes detected. Conclusion This study demonstrates the prevalence, seasonal distribution, and genotype diversity of EV circulating in children hospitalized with acute gastroenteritis in Chiang Mai, Thailand during the period 2015 to 2018.
Keywords: Gastroenteritis; Diarrhea; Enterovirus; Genotyping; Children; Thailand